Pace mapping in the atrium using bipolar electrograms from widely spaced electrodes. Issue 5 (20th March 2015) - Selvaraj, Raja J.; Yerram, Sreekanth; Kumar, Pradeep; Satheesh, Santhosh; Pillai, Ajith Ananthakrishna; Saktheeswaran, Mahesh Kumar; Balachander, Jayaraman
Abstract: Background: Pace mapping is a useful tool but is of limited utility for the atrium because of poor spatial resolution. We investigated the use of bipolar electrograms recorded from widely spaced electrodes in order to improve the resolution of pace mapping. Methods: This prospective study included patients undergoing a clinical electrophysiology study. Unipolar pacing from either the superior or inferior lateral right atrium was performed to simulate atrial tachycardia. Twelve‐lead electrocardiograms were recorded during pacing as a template. In addition, three intracardiac bipolar electrograms from a set of widely spaced electrodes were also recorded. Subsequently, unipolar pacing was performed from electrodes at known distances from the initial pacing site, and the morphology of P waves in the electrocardiogram and bipolar electrograms were compared with that of the template. Morphological comparison was performed by a cardiologist and by automated computerized matching. Spatial resolution was calculated as the minimum distance at which there was no match. Results: Fifteen patients participated in the study. Distance at which differences in morphology were noted was smaller in the bipolar electrograms compared to that indicated by P waves in the electrocardiogram, when matched by the cardiologist (6.1±3.8 mm vs. 9.9±5.2 mm, p =0.012) or by automated analysis (4±0 mm vs. 9.9±4 mm, p <0.001). Conclusions: Use of three bipolar electrograms recorded from a set of widely spaced electrodes in the right atrium improves the resolution of pace mapping compared to that using P waves from surface electrocardiograms alone.